2018
DOI: 10.1016/j.bbmt.2017.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism in Pediatric Hematopoietic Cell Transplant: A Multicenter Cohort Study

Abstract: Hematopoietic cell transplant (HCT) is associated with a proinflammatory, procoagulant environment that places recipients at increased risk of venous thromboembolism (VTE). Although the incidence of VTE in adult HCT recipients has been extensively studied, similar data for children are lacking. We conducted a multicenter retrospective study to analyze the prevalence of VTE and associated risk factors in a large cohort of patients who underwent HCT at tertiary care US children's hospitals. The Pediatric Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…This may have been due to the small number of OCP‐treated patients in either cohort (Tables 1 and 3). An increased rate of VTE after HSCT, particularly after allogeneic transplants, has been reported 18 ; however, the association showed significance only in our univariate analysis of the PHIS cohort (Table 4). HSCT in patients with primary CNS tumors is universally autologous, which may explain the lack of association between HSCT and VTE in our study.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This may have been due to the small number of OCP‐treated patients in either cohort (Tables 1 and 3). An increased rate of VTE after HSCT, particularly after allogeneic transplants, has been reported 18 ; however, the association showed significance only in our univariate analysis of the PHIS cohort (Table 4). HSCT in patients with primary CNS tumors is universally autologous, which may explain the lack of association between HSCT and VTE in our study.…”
Section: Discussionmentioning
confidence: 63%
“…Data for this study were obtained from the PHIS, which is an administrative database that contains data from inpatient, ambulatory surgery, emergency department, and observation encounters at 52 tertiary care children's hospitals in the United States 16,17 . The PHIS database has been previously described 3,18 . This part of the study was deemed exempt by the NCH IRB; permission to use the PHIS data was granted by the Children's Hospital Association.…”
Section: Methodsmentioning
confidence: 99%
“…TEs are associated with increase in morbidity and mortality, as well as increased utilization of health resources, even after consideration of cancer type and stage. 6,22,35 TEs can also delay or truncate cancer treatment 18 and lead to CVC replacements. 4 Anti-thrombotic therapy for TE is associated with adverse effects, such as increased risk of major bleeding, reported to occur between 0.3 and 24% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several potential risk factors for TEs such as sex, diagnostic era and presence of metastatic or intra-thoracic disease had variable impact in different settings. For example, Lipay et al had identified male sex as a risk factor of TEs in cancer, 11 while another study observed a non-statistically significant increase of TEs in female HSCT recipients 22 and some studies found no impact of sex on TEs. 17,18 Our study reaffirms the contribution of certain risk factors such as older age and underlying type of malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation